Identification of potential urban development areas and extraction of urban land use information based on open source data - Xu, Shaojuan; Manzke, Nina; de Lange, Norbert; Zülsdorf, Jan; Kada, Martin; Ehlers, Manfred (International Conference “Environmental Engineering”, 2017)
The optimization of urban land use is a very important aspect of sustainable urban development, including recycling abandoned land and further developing in-use areas. However, limited knowledge of these kinds of areas and their properties have been restricting end-users from exploring and reusing them. URBIS (URBan land recycling Information services for Sustainable cities) is a European project aimed at identifying urban areas which have potential to be further developed, as well as to extract their land use information based on open spatial data. URBIS first selected and stored possible sites as polygons in a Green or Grey Layer. In a second step, the information about the sites like size, vegetation coverage, and transportation connections are also calculated and attached as attributes to the polygons. At the end, the project results are presented through online services giving end-users the possibility to not only view all these areas but also select their own areas of interest according to particular attributes. The URBIS strategy has been successfully implemented in three pilot cities already. Since the methodology and the service system developed in the project are based on open source data and open source software, URBIS could easily be expanded to other European cities.
Keywords: vacant land; brownfield; open geospatial data